2019
DOI: 10.1039/c8fo02319k
|View full text |Cite
|
Sign up to set email alerts
|

Effects of omega-3 polyunsaturated fatty acids on steroidogenesis and cellular development in PCOS rats

Abstract: Polycystic ovary syndrome (PCOS) is a common endocrine disorder, which is characterized by hyperandrogenism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Letrozole, an aromatase inhibitor, induces hyperandrogenemia by reducing the conversion of T to estrogen ( 49 ). Accumulated human and animal studies have demonstrated that omega-3 PUFAs docosahexenoic acid (DHA) and eicosapntemacnioc acid (EPA) may ameliorate PCOS progression ( 50 , 51 ). Anovulation was dramatically improved by DHA supplementation ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Letrozole, an aromatase inhibitor, induces hyperandrogenemia by reducing the conversion of T to estrogen ( 49 ). Accumulated human and animal studies have demonstrated that omega-3 PUFAs docosahexenoic acid (DHA) and eicosapntemacnioc acid (EPA) may ameliorate PCOS progression ( 50 , 51 ). Anovulation was dramatically improved by DHA supplementation ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…44 Moreover, omega-3 was reported to prevent the reduction of plasma testosterone level by inhibiting 5 alpha-reductase with subsequent prevention of conversion of testosterone to dihydrotestosterone. 45 Hu et al 46 demonstrated that omega-3 potentiates the cellular development and steroid biosynthesis via CYP51 up-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented the antioxidant, anti-apoptotic of omega 2 fatty acids and proved that omega-3 produced a highly significant decrease in the percentage of oxidative damage and cell death. 35,42,46,50,56,76…”
Section: Discussionmentioning
confidence: 99%
“…In management of PCOS women, especially for PCOS patients with obesity, lifestyle and nutrition interventions and weight loss are the first step in the recommendations of treatment in the guidelines [6] . Among dietary management for PCOS, omega-3 fatty acids play an important role in weight loss, improving insulin sensitivity and ovulation enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…[5] The only essential types of all dietary fatty acids are omega-3 and 6 polyunsaturated fatty acids; because all other fatty acids can be synthesized from the other shorter chain fatty acids in the human body. [6] Polyunsaturated fatty acids (PUFAs) have 16 to 22 carbon atoms and more than one double bond. The longchain omega-3 Poly unsaturated fatty acids; namely, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) have many crucial effects in human health.…”
Section: Introductionmentioning
confidence: 99%